Lexical matrices within the framework of sociolinguistic and psycholinguistic theory: a case study of French–English code-switching - Olga Kosovych; Косович Ольга; Kosovych Olga; Olena Shon; Шонь Олена; Shon Olena (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. This article explores the phenomenon of French–English code-switching within the framework of psycholinguistic theory, offering a comprehensive analysis of its cognitive, linguistic, and sociolinguistic dimensions. Code-switching, defined as the alternation between two or more languages within a single communicative act, is examined through foundational theories from scholars like U. Weinreich, S. Poplack, J.J. Gumperz, and K. de Bot. The study delves into psycholinguistic models, such as Levelt’s speech production framework, which outlines stages like conceptual preparation, grammatical encoding, phonological encoding, and articulation. De Bot’s bilingual lexicon model suggests that lexicons of different languages form interconnected subsystems within a unified framework, enabling seamless code-switching through lemma selection and word-form retrieval. The concept of the matrix language, introduced by F. Grosjean, highlights how bilingual speakers operate in monolingual or bilingual modes, with co-activation of languages facilitating dynamic linguistic transitions.Linguistically, the article addresses constraints like S. Poplack’s equivalence constraint, whichensures structural compatibility, and J. MacSwan’s minimalist approach, which views code-switching as the merging of lexicons within a unified grammatical system. Challenges to rigid constraints, such as the government principle, reveal the flexibility ofbilingual speech, influenced by social and pragmatic factors. French–English code-switching, prevalent in fashion and lifestyle media, exemplifies how French terms like laissez-faire, je ne sais quoi, and rendezvous are integrated into English discourse to evoke sophistication and cultural prestige. These terms often function as borrowings or code-switches, reflecting bilingual competence and cultural signaling.Sociolinguistically, code-switching serves as a marker of identity and prestige, particularly in globalised contexts. The article emphasises the cognitive flexibility of bilinguals, as noted by E. Bialystok, and the role of social context in shaping language choice, as discussed by P. Auer and B. Spolsky. Examples from media texts illustrate how French terms enhance rhetorical expressiveness while adhering to English grammatical norms. The study concludes that French–English code-switching reflects a complex interplay of cognitive processes, linguistic structures, and cultural dynamics, offering insights into bilingual communication and its role in modern discourse.

Резюме. У статті досліджено феномен франко-англійського кодового перемикання в рамках психолінгвістичної теорії, пропоновано всебічний аналіз його когнітивних, лінгвістичних та соціолінгвістичних аспектів. Кодове перемикання, визначене як чергування двох або більше мов у межах однієї комунікативної взаємодії, розглянуто через фундаментальні теорії У. Вайнрайха, С. Поплак, Дж. Дж. Гамперза та К. де Бота. Увагу зосереджено на психолінгвістичнімоделі, зокрема модель мовленнєвого продукування У.Левелта, яка включає етапи концептуальної підготовки, граматичного кодування, фонологічного кодування та артикуляції. Модель двомовного лексикону К. де Бота припускає, що лексикони різних мов утворюють взаємопов’язані підсистеми в єдиній структурі, що забезпечує плавне кодове перемикання через вибір лем та пошук словесних форм. Концепція матричної мови, запропонована Ф. Грожаном, підкреслює, як двомовні мовці функціонують у мономовному або двомовному режимах, а коактивація мов сприяє динамічним лінгвістичним переходам. З лінгвістичної перспективи проаналізовано обмеження, такі як правило еквівалентності С. Поплак, що забезпечує структурну сумісність, та мінімалістичний підхід Дж. МакСвана, який розглядає кодове перемикання як злиття лексиконів у єдиній граматичній системі. Виклики строгим обмеженням, як-от принцип управління, свідчать про гнучкість двомовного мовлення, на яку впливають соціальні та прагматичні чинники. Франко-англійське кодове перемикання, поширене в медіа про моду та стиль життя, демонструє, як французькі терміни, такі як laissez-faire, je ne sais quoiта rendezvous, інтегруються в англійський дискурс для створення відчуття вишуканості та культурного престижу. Ці терміни часто функціонують як запозичення або кодові перемикання, відображаючи двомовну компетенцію та культурну сигналізацію. Кодове перемикання є маркером ідентичності та престижу, особливо в глобалізованих контекстах. Підкреслено когнітивну гнучкість двомовних мовців, як зазначаєЕ. Бялісток, та роль соціального контексту у виборі мови, як обговорюють П. Ауер та Б. Сполскі. Приклади з медіа текстів ілюструють, як французькі терміни посилюють риторичну виразність, зберігаючи англійські граматичні норми. Наголошено на тому, що франко-англійське кодове перемикання відображає складну взаємодію когнітивних процесів,лінгвістичних структур і культурних динамік, надаючи цінні інсайти про двомовну комунікацію та її ролі в сучасному дискурсі.

A tanulmány a francia–angol kódváltás jelenségét vizsgálja, átfogó elemzést nyújtva annak kognitív, nyelvi és szociolingvisztikai dimenzióiról. A kódváltás, amelyet két vagy több nyelv váltakozásaként definiálunk egyetlen kommunikációs aktuson belül, olyan alapvető elméletek alapján kerül bemutatásra, mint U. Weinreich, S. Poplack, J. J. Gumperz és K. de Bot munkái. A kutatás a pszicholingvisztikai modellekbe, például Levelt beszédprodukciós keretébe is betekintést nyújt, amely olyan szakaszokat ír le, mint a fogalmi előkészítés, a grammatikai kódolás, a fonológiai kódolás és az artikuláció. De Bot kétnyelvű lexikon modellje szerint a különböző nyelvek lexikonjai egyetlen egységes rendszerben egymással összekapcsolt alrendszereket alkotnak, ami lehetővé teszi a zökkenőmentes kódváltást a lemma kiválasztása és a szóalak előhívása révén. F. Grosjean mátrixnyelv-fogalma kiemeli, hogy a kétnyelvű beszélők monolingvális vagy bilingvális üzemmódban működhetnek, és a nyelvek együttes aktiválása elősegíti a dinamikus nyelvi átmeneteket. Nyelvészeti szempontból a cikk olyan koncepciókkal is foglalkozik, mint S. Poplack ekvivalencia-korlátja, amely a szerkezeti kompatibilitást biztosítja, valamint J. MacSwan minimalista megközelítése, amely a kódváltást a lexikonok összeolvadásaként értelmezi egy egységes nyelvtani rendszerben. A kétnyelvű beszéd rugalmasságát társadalmi és pragmatikai tényezők is befolyásolják. A francia–angol kódváltás, amely gyakori a divattal és életstílussal foglalkozó médiában, jól példázza, hogyan épülnek be a francia kifejezések –mint a laissez-faire, je ne sais quoivagy rendezvous–az angol diskurzusba, hogy kifinomultságot és kulturális presztízst sugalljanak. Ezek a kifejezések gyakran kölcsönszóként vagy kódváltásként funkcionálnak, tükrözve a kétnyelvű kompetenciát és a kulturális hátteret. Szociolingvisztikai szempontból a kódváltás az identitás és a presztízs jelölőjeként szolgál, különösen a globalizált világban. A tanulmány hangsúlyozza a kétnyelvűek kognitív rugalmasságát (E. Bialystok), valamint a társadalmi kontextus szerepét a nyelvválasztásban (P. Auer, B. Spolsky). Médiaszövegekből vett példák szemléltetik, hogyan fokozzák a francia kifejezések a retorikai kifejezőerőt, miközben alkalmazkodnak az angol nyelvtani normákhoz. A szerzőkarra a következtetésre jutnak, hogy a francia–angol kódváltás a kognitív folyamatok, a nyelvi struktúrák és a kulturális dinamikák összetett kölcsönhatását tükrözi, betekintést nyújtva a kétnyelvű kommunikációba és annak szerepébe a modern diskurzusban.
Лексичні матриці в рамках соціолінгвістичної та психолінгвістичної теорії: приклад перемикання кодів між французькою та англійською мовами
Lexikai mátrixok a szociolingvisztikai és pszicholingvisztikai elméletek keretében: a francia–angol kódváltás példája
Teljes kiadvány: https://aab-philologica.kmf.uz.ua/aabp https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00016332
Keywords: code-switching; psycholinguistics; bilingualism; matrix language; lexical retrieval; French–English; sociolinguistics; grammatical constraints